Back to Planning How to Close Brazil's Infrastructure Gap in Times of Austerity - Raiser, Martin (Other Infrastructure Study, 2017)
Why does Brazil continue to lag its peers in the quality of physical infrastructure? What are the implications for growth prospects? What could be done to close the infrastructure gap? These are the key questions addressed in this new report on infrastructure in Brazil. The key argument of the report is that Brazil needs to improve its capacity to plan and prioritize its infrastructure investments. Poorly prioritized and prepared infrastructure investments are a key reason why successive government programs, often with significant budget allocations, have had limited impact. Insufficient planning efforts have meant that what investment takes place has done little to reduce glaring inefficiencies and losses. With more efforts upstream to prepare a robust pipeline of projects, Brazil is in an excellent position to attract commercial financing to its infrastructure. With more attention to sector planning and governance, losses could be reduced and the effective resources available to infrastructure could be roughly doubled. This in turn would help boost growth and improve the quality of public services without the need for much additional public money. The report analyzes recent government measures such as the creation of the PPI and develops recommendations how infrastructure can become an engine of economic recovery in Brazil